Bispecific antibody target pair discovery by high-throughput phenotypic screening using in vitro combinatorial Fab libraries - Pallavi Bhatta; Kevin D. Whale; Amy K. Sawtell; Clare L. Thompson; Stephen E. Rapecki; David A. Cook; Breda M. Twomey; Milena Mennecozzi; Laura E. Starkie; Emily M. C. Barry; Shirley J. Peters; Ahmad M. Kamal; et al. (Taylor & Francis Group, 2021)
Bispecific antibodies can uniquely influence cellular responses, but selecting target combinations for optimal functional activity remains challenging. Here we describe a high-throughput, combinatorial, phenotypic screening approach using a new bispecific antibody target discovery format, allowing screening of hundreds of target combinations. Simple in vitro mixing of Fab-fusion proteins from a diverse library enables the generation of thousands of screen-ready bispecific antibodies for high-throughput, biologically relevant assays. We identified an obligate bispecific co-targeting CD79a/b and CD22 as a potent inhibitor of human B cell activation from a short-term flow cytometry signaling assay. A long-term, high-content imaging assay identified anti-integrin bispecific inhibitors of human cell matrix accumulation targeting integrins β1 and β6 or αV and β1. In all cases, functional activity was conserved from the bispecific screening format to a therapeutically relevant format. We also introduce a broader type of mechanistic screen whereby functional modulation of different cell subsets in peripheral blood mononuclear cells was evaluated simultaneously. We identified bispecific antibodies capable of activating different T cell subsets of potential interest for applications in oncology or infectious disease, as well as bispecifics abrogating T cell activity of potential interest to autoimmune or inflammatory disease. The bispecific target pair discovery technology described herein offers access to new target biology and unique bispecific therapeutic opportunities in diverse disease indications.